Self-adaptive proximal algorithms for equilibrium problems in Hadamard space - Semenov, Vladimir V.; Chernorai, Vladislava; Denysov, Serhii (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2025)
We consider a new self-adaptive algorithms for equilibrium problem in Hadamard spaces. At each step of the algorithms, the sequential minimization of two special strongly convex functions is performed. Our self-adaptive algorithms do not calculate bifunction values at additional points and do not require knowledge of bifunctions' Lipschitz constants. For pseudomonotone bifunctions of Lipschitz-type, theorems on weak convergence of sequences generated by algorithms are proved.